2021
DOI: 10.1016/j.soard.2021.03.020
|View full text |Cite
|
Sign up to set email alerts
|

Cost-effectiveness of bariatric surgery versus community weight management to treat obesity-related idiopathic intracranial hypertension: evidence from a single-payer healthcare system

Abstract: Background: Idiopathic intracranial hypertension (IIH) is associated with significant morbidity, predominantly affecting women of childbearing age living with obesity. Weight loss has demonstrated successful disease-modifying effects; however, the long-term cost-effectiveness of weight loss interventions for the treatment of IIH has not yet been established. Objectives: To estimate the cost-effectiveness of weight-loss treatments for IIH. Setting: Single-payer healthcare system (National Health Service, Englan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 26 publications
0
12
0
Order By: Relevance
“…Although bariatric surgery in IIH:WT had high upfront costs, 28 it was more cost-effective with time, both saving money and improving the quality of life at the 5-, 10-, and 15-year time horizons considered. 29 This analysis provides further evidence for considering different types of weight loss methods, supporting bariatric surgery as a management option to be considered in women with active IIH. Bariatric surgery procedures vary in their weight loss outcomes their effect on obesity complications and weight loss.…”
Section: Discussionmentioning
confidence: 79%
“…Although bariatric surgery in IIH:WT had high upfront costs, 28 it was more cost-effective with time, both saving money and improving the quality of life at the 5-, 10-, and 15-year time horizons considered. 29 This analysis provides further evidence for considering different types of weight loss methods, supporting bariatric surgery as a management option to be considered in women with active IIH. Bariatric surgery procedures vary in their weight loss outcomes their effect on obesity complications and weight loss.…”
Section: Discussionmentioning
confidence: 79%
“…The significant improvement of AHI with bariatric surgery and its superiority to CWI is in line with large clinical trials and meta-analyses proposing that bariatric surgery is a definite treatment for OSA in many other patient cohorts [ 17 ]. We have also demonstrated the clinical and cost effectiveness of bariatric surgery for treating IIH [ 19 , 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Headaches associated with IIH are problematic, debilitating, and persistent [12][13][14]. Weight loss is currently the only known disease modifier in IIH [15] and the recent IIH Weight Trial showed that bariatric surgery was superior over community weight management in lowering the intracranial pressure [16] with it also being cost-effective [17]. Maintenance of weight loss especially by dietary means can be difficult [3].…”
Section: Introductionmentioning
confidence: 99%